Mobile health solutions for biomedical applications - Olla, Phillip; Tan, Joseph K. H.; Gale Group (Hershey, Penn. Medical Information Science Reference, 2009)
Provides an international perspective on the benefits of mobile health technology and describes different examples and applications implemented in global healthcare. Presents research on the emergence of pervasive computing and health care systems that provide quality patient care services.
"This book gives detailed analysis of the technology, applications and uses of mobile technologies in the healthcare sector by using case studies to highlight the successes and concerns of mobile health projects"--Provided by publisher.
Evaluation of two mobile nutrition tracking applications for chronically ill populations with low literacy skills -- Accessing an existing virtual electronic patient record with a secure wireless architecture -- Evaluation criteria for mobile personal health records implementation -- Medical information representation framework for mobile healthcare -- A distributed approach of a clinical decision support system based on cooperation -- Managing mobile healthcare knowledge: physicians' perceptions on knowledge creation and reuse -- Patient monitoring in diverse environments -- Monitoring hospital patients using ambient displays -- Towards easy-to-use, safe, and secure wireless medical body sensor networks -- Sensing of vital signs and transmission using wireless networks -- Towards wearable physiological monitoring on a mobile phone -- A framework for capturing patient consent in pervasive healthcare applications -- Technology enablers for context-aware healthcare applications -- Modeling spatiotemporal developments in spatial health systems -- Context-aware task distribution for enhanced M-health application performance.
Electronic reproduction.
Keywords: Telecommunication in medicine; Mobile communication systems; Wireless communication systems; Cell phones; Medical technology; Electronic books